Indole Compounds Related to Auxins and Goitrogens of Woad (Isatis tinctoria L.) - Elliott, Malcolm C. (1971)
Five conspicuous indole derivatives are present in leaves and other tissues of woad (Isatis tinctoria L.). They were identified as tryptophan, isatan B, glucobrassicin, neoglucobrassicin, and glucobrassicin-1-sulfonate. The latter three indole glucosinolates are present at levels of at least 260, 69, and 200 milligrams per kilogram fresh weight and were isolated as crystalline salts. Comparison of physical and chemical properties, particularly NMR spectral analysis, confirms that the 1-methoxyglucobrassicin structure suggested for neoglucobrassicin is correct, whereas further evidence for the even more unusual sulfonation of the ring nitrogen in glucobrassicin-1-sulfonate was obtained. Glucobrassicin-1-sulfonate has an enzymic degradation pattern identical to that of glucobrassicin. As it too releases thiocyanate, it must be added to the list of known plant goitrogens. These studies and the techniques described establish woad as exceptionally suitable higher plant material for metabolic studies of indoles related to goitrogens and auxins.